(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to evaluate the natural regeneration potential of Phoenician juniper ( Juniperus phoenicea ) and to assess the influence of environmental conditions and and human activities on its reproduction and growth in the Sidi Khaled area , west of Derna city . Two sites where the species occurs in relatively good condition were selected , and each covering 500 m2 . All trees and seedlings were inventoried , and canopy cover of J. phoenicea as well as associated vegetation was measured . Seedling abundance was monitored over four annual surveys . At Site 1 , seedling numbers declined progressively after the first survey , which recorded 13 seedlings in plot A and 8 in plot B . At Site 2 , initial seedling numbers were lower ( 7 in plot A and 6 in plot B ) , and complete seedling disappearance was observed by the third and fourth surveys . Site 2 exhibited lower vegetation density and greater disturbance due to its proximity to residential areas . Overall , the results indicate that drought exerts a stronger negative effect on Phoenician juniper regeneration than livestock grazing . Although adult trees appear healthy , limitations in natural growth reduce their ability to regenerate and sustain population continuity over time .